Arcing fault recognition using spectral analysis method - Gholami, Majid (2009)
In transmission lines while one fault happens it’s crucial to recognize the kind and the type it belongs to. This means it must be indentified whether it is transient or permanent. The methods for recognizing these faults can be categorized into two varieties. First, in the dead time of recloser and second during faults. This project studies the second method which has the capability to recognize the type of fault during the fault, means before the breaker’s opening, which is called spectral analysis method. In this project programming of arcing faults recognition base on spectral analysis method was presented in ATP and MATLAB software. Then, the most frequent single-phase to ground fault on transmission line was considered and results were evaluated with and without the fault resistance into fault model. Ultimately, it is concluded that spectral analysis method operates sooner than previous methods for arcing fault recognition that can improve the power system transient stability and reliability. Furthermore, it provides much higher service continuity to the costumers.